Study On Chlorophyll’s Concentration Dependency Towards Electrical Characteristics Of Banana Midrib-Based Dye-Sensitized Solar Cell For Waste Management Solution - Rahayu, Rahmad (2022)
The application of banana midrib waste chlorophyll as an alternative natural dye in Dye Sensitized Solar Cell (DSSC) could be advantageous. DSSC is a technology that contributes to a renewable energy source, which is environmental-friendly and low in cost. The effect of different dye concentrations on the performance of Dye-Sensitized Solar Cells (DSSC) has been studied. The natural colours utilised in this study were derived from the chlorophyll of the banana midrib. TiO₂, chlorophyll and KI serve as a working electrode, photosensitizer and electrolyte in the DSSC respectively. Doctor Blade techniques were employed to make the functional electrode. Besides that, Dye-Sensitized Solar Cell (DSSC) is the third-generation solar cell that manipulates the concept of plant’s photosynthesis in order to harvest the energy from the sunlight in whatever condition though during the low irradiance or light intensity. Chlorophyll, which can be extracted from majority of greeny plants, is one of the important substances in absorbing the light for energy harvesting. Since the concentration level of chlorophyll defers for each type, age or part of the plants, numerous studies related to these scopes have been actively performed. In this study, banana midrib that are mostly common waste are left because banana leaves are used as aroma in the packaging of Nasi Lemak, Lemang, Tapai and traditional foods. Hereby, will be benefited to extract different concentration levels of chlorophyll for the fabrication of DSSCs' purpose. The relationship between the chlorophyl’s concentration level and the output of electrical properties will be further analyzed.